2020
DOI: 10.1021/acs.molpharmaceut.0c00980
|View full text |Cite
|
Sign up to set email alerts
|

New Small-Molecule Glycoconjugates of Docetaxel and GalNAc for Targeted Delivery to Hepatocellular Carcinoma

Abstract: In this work, we have developed covalent and low molecular weight docetaxel delivery systems based on conjugation with N-acetyl-d-galactosamine and studied their properties related to hepatocellular carcinoma cells. The resulting glycoconjugates have an excellent affinity to the asialoglycoprotein receptor (ASGPR) in the nanomolar range of concentrations and a high cytotoxicity level comparable to docetaxel. Likewise, we observed the 21–75-fold increase in water solubility in comparison with parent docetaxel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…This may be because ASGPR on the cell membrane was almost saturated by galactose, being consistent with our previous experiments. It was reported that monovalent N -acetyl- d -galactosamine (GalNAc) or trivalent (GalNAc) 3 can competitively inhibit the uptake of GalNAc-conjugated docetaxel in HepG2 cells, also supporting our results. Clearly, the hepatocyte-targeting capacity of prodrugs ( W-1-5, W-2-9 , and W-3-8) is driven by the specific recognition of the galactose group toward ASGPR.…”
Section: Resultssupporting
confidence: 91%
“…This may be because ASGPR on the cell membrane was almost saturated by galactose, being consistent with our previous experiments. It was reported that monovalent N -acetyl- d -galactosamine (GalNAc) or trivalent (GalNAc) 3 can competitively inhibit the uptake of GalNAc-conjugated docetaxel in HepG2 cells, also supporting our results. Clearly, the hepatocyte-targeting capacity of prodrugs ( W-1-5, W-2-9 , and W-3-8) is driven by the specific recognition of the galactose group toward ASGPR.…”
Section: Resultssupporting
confidence: 91%
“…Typical targeting ligands mainly include antibodies, folic acid, galactose/lactose and some oligopeptides. [14][15][16] The galactosyl receptor, asialoglycoprotein receptor (ASGPR), is abundant on the surface of liver tumor cells. Therefore, the carrier modified with galactose could introduce active targeting capability and convenient internalization through endocytosis of liver tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Two N -acetylgalactosamine derivatives A and B were used as structural blocks to produce atorvastatin conjugates (Scheme 1). Azides A and B were previously successfully applied by our group for the synthesis of several antitumor drug conjugates (doxorubicin, 14 paclitaxel, 15 and docetaxel 16 ). Therefore, in this work the ligands were obtained using the earlier elaborated techniques.…”
Section: Resultsmentioning
confidence: 99%